Who bears the burden of social security contributions in Germany? Evidence from 35 years of administrative data - Kai-Uwe Müller; Michael Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper provides evidence over a long time period on the question of who bears the burden of social security contributions (SSC) in Germany. Following Alvaredo et al. (2016) we exploit kinks in the budget set generated by a drop in the marginal SSC rate at earnings caps. Based on cross-sectional earnings distributions the framework does not rely on policy reforms. Applying the approach to administrative data for West Germany facilitates a comprehensive incidence analysis between 1975 and 2010. We find that neither employers nor employees shift a substantial part of their SSC burden. These results are consistent over the whole time period and in robustness checks corroborating previous findings. A small trend towards a slight increase in the SSC burden falling on employees is not statistically significant.
Keywords: H22; J38; H55; 330; incidence; social security contributions; discontinuities